Documentación on line sobre libro antiguo - Bas Martín, Nicolás (Documentación de las Ciencias de la Información, 2007)
In a world in which the analogue is fast being abandoned in favour of the digital, we need to look back in order not to forget our origins and our textual culture. While a number of authors have insisted on seeing a clash between old and new, the Internet has in fact had only a qualified impact on fields such as that of antique books. It is true that the Internet has provided useful tools for improving our knowledge of European cultural production from the Middle Ages to the nineteenth century. However, not everything found on the Web is useful, and we therefore need suitable criteria, instruments and information sources to help us improve our understanding of the fascinating world of antique books.